The Changes evolved in the Spatial Organization at Border Regions: With special emphasis on the role played by acting agents A Case Study on: Baneh and its peripheries - Mehdi Razpour (پژوهش‌های برنامه و توسعه)
Today, urban and regional planning has evolved into a complex process in which a group of acting agents and decision-makers decide about the current and future status qua of the city and region. Due to this change in the planning system, the position of a planner has changed from a skilled technician and decision maker to a facilitator who play a coordinating role between different acting agents in regard to their conflicting interests. Planning practices in border regions are undergoing a different course due to dominance of different acting agents initiating and implementing the decisions on the status quo of the city and its periphery. As such it has affected the developments of the spatial organization in these regions. cross-border interactions opportunities and the governance influenced by a network of actors over the border economy has undergone extensive changes in the case of Border County space organization (Baneh, Kurdistan province) both at micro and macro spaces in the past years. These changes seem to be untenable because of many internal and external influencing factors and the role played by local, regional and national actors in this regard. As such many changes has emerged in the spatial organization of the city Baneh and its periphery. This paper has aimed to explain how the acting agents have had influencing effects on the changes in Baneh Border County space organization. This case study is qualitative in nature. Two rounds of Delphi technique were used to select indicators for the measurement of the changes in the space organization. Relationships between the actors network were assessed using Actors Network Theory (ANT) and UciNet software. The results of this study show that actors can change the organizations in a region many times due to their power and influence.